Konsep Al-Kaṣb Dalam Al-Qur’an (Studi Tafsir Mafātīḥ al-Ġayb Karya Fakhr al-Dīn al-Rāzī) - Intan Sari, Desi; Malik Ghozali, Abdul; Masruchin, Masruchin (MISYKAT: Jurnal Ilmu-ilmu Al-Quran Hadist Syari'ah dan Tarbiyah, 2023)
The purpose of this study is to find out the differences in kaṣb thought or other views of Fakhr al-Dīn al-Rāzī with Ash'ari. This study departs from the problem of whether there is a relationship between God's will and human actions according to Fakhruddin Al-Rāzī and whether Al-Rāzī's view of kaṣb is the same as that of Ash'ari. This research is a library-based research that starts from understanding interpretations related to human actions, in this case human actions are analyzed in the book of tafsir Mafatih Al-Ghaib. The findings of the study concluded that Al-Rāzī's idea or view of human actions (kaṣb) was that Al-Rāzī neither accepted nor completely rejected the theory of Ash'ari kaṣb which he called "a word for meaningless concepts". Al-Rāzī had his own view of kaṣb which according to Al-Razi kaṣb was the object of qadar created by Allah Almighty directly and newly, without any cause or other factor influencing it. Examples are the creation of man, heaven, earth and everything miraculous. Ar-Rāzī also defines kasb as an object of qadar that replaces qudrah meaning as an object created by utilizing forces or factors that already exist. In this case, Allah Almighty uses His qudrah or ability to create the object. An example is the creation of trees, animals, and humans born from the process of pregnancy. The basis of ar-Razi's refutation is that man has no ability to create or prevent the causal factors (al-Da'i) that lead to action.